SISTEM UJIAN ONLINE SELEKSI PENERIMAAN MAHASISWA BARU DENGAN PENGACAKAN SOAL MENGGUNAKAN LINEAR CONGRUENT METHOD (Studi Kasus di Universitas Muhammadiyah Bengkulu) - Gunawan Gunawan; Dedy Agung Prabowo (Universitas PGRI Semarang, 2017)
In the data processing of examination/test system for new students' entrance in Muhammadiyah University of Bengkulu had been using computer facility for method of input the result of test when the test implementation still using paper sheets (conventional).In the process of writing thesis, the author discusses about how to create items that will be done by testee are not same as the others, its mean the number of that test items will be random so the testee are more coducive in implementation of test.Online examination/test system is designed by using the Unified Modeling Language (UML). It hoped can be used to overcome the problems in the selection test of new students' entrance and can be fully utilized and feasible to be used in order to achieve system that is accurate, fast, precise and more effective. Linear Congruent Method (LCM) is a method that generates random numbers are widely used in computer programs. In this method, repetition in spesific time period or after a few times of generation.This is one of main characteristic from this method. Determination of the constants in LCM very determine whether good or not the random numbers obtained. In the sense of obtaining random numbers as if there will be no repetition. Using of LCM method in this case is simply to randomization number of items in order to every students who did a test selection run with effective.